PENGEMBANGAN POSTER SUBMATERI PERAN TUMBUHAN DI BIDANG EKONOMI UNTUK PEMBUATAN MUFFIN PISANG - Rahayu, Iis Mufidah; Daningsih, Entin; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aimed to determine the feasibility of poster media for the laboratory work of making banana muffins in submaterial of the plant role in economy and to know students responses to poster media. This research was uses research and development (R&D) method consisting of six out from ten stages, namely potential and problems, data collection, product design, design validation, design revision and limited product trials. Poster media were validated by two lecturers from biology education and three biology teachers from senior high school. The validation divided was conducted into two steps. The first step was validation of poster media instrument and the second step was poster media validation. The students response to the poster media was used a questionnaire and categories according to Likert. Based on validation results of the poster media using twelve criteria, the score was 0.99 of CVI value, and categories valid. Therefore the poster media for submaterial plant role in economy was feasible tobe use in learning proccess. The student response to poster media achieve 89,7% and categories very high. Keywords: Banana Muffin, Feasibility, Poster, R&D Method, Responses